Development of High Power LED Driver Using LTSpice Software - Muhammad Ikram, Mohd Rashid; Suliana, Abd Ghani; Mohamad Fakhrudin, Sulaiman Mustahim (2013)
LED technology has been used widely in various applications due to its advantage in term of functionality, high efficiency, low cost, small size and high reliability. In order to improve LED performance and prolong LED’s life, High Power LED driver is been developed. LED driver is used to control output voltage by using current mode controlled method. This development of LED driver can increase the LED operation efficiency, provide high voltage protection, decreases the driver size and lastly make possible of user friendly installation. Voltage source is step up by using boost converter as main circuit. In control circuit, current mode controlled is used to regulate output characteristic of High Power LED. LTC 3783 is used as PWM controller to drive the gate and provide pulse signal to the MOSFET. This driver is designed to operate load that consists of 6 units LED each rating of 5 Watt connected in series. Theoretical calculation is made to obtain component specification. The LTspice software is used to simulate the driver circuit by using calculated parameters before move on to hardware implementation. Eagle software is used to design the Printed Circuit Board (PCB). Then, all components are mounted on the PCB which is made of FR4 material. The hardware built is tested experimentally and the output waveform is recorded.